The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s1415-47572006000400001
|View full text |Cite
|
Sign up to set email alerts
|

Stages in the evolution of the Hardy-Weinberg law

Abstract: The Hardy-Weinberg law has been used widely for about one hundred years with little question as to the foundations laid down by its originators. The basic assumption of random mating, that is choice of mates by a process akin to that of a lottery, was shown to produce genotypic proportions following the "binomial-square" rule, the so-called Hardy-Weinberg proportions (HWP). It has been assumed by many that random mating was the only way of pairing genes capable of producing HWP. However it has been shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…However, he was in the vanguard of efforts to exploit Mendelism to advance human and medical genetics. For example Weinberg (1908) was a notable contribution to the genetics of twinning in man (Stark 2006). A few writers, such as the late James Crow, did appreciate his work (Crow 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, he was in the vanguard of efforts to exploit Mendelism to advance human and medical genetics. For example Weinberg (1908) was a notable contribution to the genetics of twinning in man (Stark 2006). A few writers, such as the late James Crow, did appreciate his work (Crow 1999).…”
Section: Resultsmentioning
confidence: 99%
“…At about that time he started to produce an impressive list of publications, since his activities and contacts as a medical practitioner gave him access to medical data and provided a stimulus to develop genetic and statistical concepts. His "Hardy-Weinberg law" article, Weinberg (1908), was a study of the genetics of twinning in humans (Stark 2006). Edwards (2008) begins with tribute to Weinberg's comprehensive formulation of the Hardy-Weinberg law.…”
mentioning
confidence: 99%
“…Surely something as déclassé as 3:1 ratios was not to be preferred to GALTON's sophisticated and seductive mathematics. (p. 1333) But we leave the last word to Mayo (2008): Li (1988), followed and elaborated by Stark (2006aStark ( , 2006b, showed that panmixia is not the only breeding structure that can yield HW proportions, so that panmixia is a sufficient but not a necessary condition for HWE. However, no natural population is known to manifest the other possible breeding structures so that it appears unlikely that they need to be considered in data collection and analysis.…”
Section: Closing Remarksmentioning
confidence: 99%
“…In the interests of completing the 'story' , we explain how this is so. As discussed below, Weinberg used the property of stability to explore the question of a possible genetic basis for the occurrence of twins in humans (Stark, 2006a).…”
mentioning
confidence: 99%
“…Weinberg (1908) used the HW distribution to analyze the inheritance of twinning in man. Stark (2006b) noted that Weinberg's analysis may need to be modified in the light of Li's paper. Stark and Seneta (2012) show that a paper of a Russian mathematician S. N. Bernstein was a fundamental, though largely unrecognized, contribution to genetic analysis by reason of its connection with the HW law.…”
mentioning
confidence: 99%